Implikasi Asas Manfaat Penyiaran Televisi terhadap Perlindungan Hak Konsumen - Widodo, Anton; Rachman, Evy eptiana; Sinthiya, Ida Ayu Putu Anggie (KOMUNIKASIA: Journal of Islamic Communication and Broadcasting, 2023)
Abstract Television media is the mass media that is most in demand by the public. The diversity of programs presented is an alternative for gaining knowledge (information) or as a means of entertainment. The development of broadcasting in the era of globalization of technology and information has made the government guarantee the implementation of television management activities in Indonesia. This development also had a negative impact on the world of broadcasting, industrial phenomena began to enter broadcasting operations. High ratings and shares are the main focus to attract a large number of commercial advertisements for profit or profit. The rights of the public as broadcasting consumers are ignored, violations of the provisions of broadcasting laws and broadcast content that are contrary to Broadcasting Behavior and Broadcast Program Standard Guidelines (P3SPS) also often occur. This problem clearly violates the rights of consumers and also ignores the principle of benefit in broadcasting.